2007
DOI: 10.1097/mjt.0b013e31813e65b7
|View full text |Cite
|
Sign up to set email alerts
|

Is Acetazolamide Similar to Topiramate for Reversal of Antipsychotic-Induced Weight Gain?

Abstract: Acetazolamide (AZD), a sulfa-like moiety, is a potent, nonspecific inhibitor of carbonic anhydrase (CA) enzymes and has been demonstrated to decrease lipogenesis in adipose cells in in vitro cell culture studies. In contrast, topiramate (a sulfamate moiety) appears to inhibit specific (CA) enzymes II and V. Four placebo-controlled trials with topiramate have demonstrated positive results in weight loss. There is only anecdotal evidence that AZD may cause weight loss. The following case is of a 49-year-old Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Potential mechanisms of topiramate's symptomatic efficacy include the following: (i) decreasing the presynaptic release of glutamate and excessive glutamate neurotransmission via kainate receptors, resulting in a blunting of the hyperdopaminergia and prolonging stimulation of AMPA/KA receptors ; and (ii) inhibition of glutamate activity, attenuating activity at Na + and Ca 2+ channels, and augmenting effects of the GABA‐A receptors . Potential mechanisms for improvement in body weight and metabolic parameters include the following: (i) attenuation of appetite via , (ii) insulin‐sensitizing effects resulting in the direct enhancement of insulin action and leading to lower glucose and insulin levels , and (iii) stimulation of the lipoprotein lipase in the adipose tissue and skeletal muscle, inhibiting carbonic anhydrase enzymes involved in several steps of de novo lipogenesis in the mitochondria and cell cytosol .…”
Section: Discussionmentioning
confidence: 99%
“…Potential mechanisms of topiramate's symptomatic efficacy include the following: (i) decreasing the presynaptic release of glutamate and excessive glutamate neurotransmission via kainate receptors, resulting in a blunting of the hyperdopaminergia and prolonging stimulation of AMPA/KA receptors ; and (ii) inhibition of glutamate activity, attenuating activity at Na + and Ca 2+ channels, and augmenting effects of the GABA‐A receptors . Potential mechanisms for improvement in body weight and metabolic parameters include the following: (i) attenuation of appetite via , (ii) insulin‐sensitizing effects resulting in the direct enhancement of insulin action and leading to lower glucose and insulin levels , and (iii) stimulation of the lipoprotein lipase in the adipose tissue and skeletal muscle, inhibiting carbonic anhydrase enzymes involved in several steps of de novo lipogenesis in the mitochondria and cell cytosol .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adverse conditions such as nausea, dyspepsia and diarrhoea may also contribute to BW loss. With regards to the biochemical mechanism, it has also been reported that topiramate may inhibit carbonic anhydrase (CAs, EC 4.2.1.1) enzymes involved in several steps of de novo lipogenesis, both in the mitochondria and cytosol of cells, which can result in BW loss . Another study demonstrated that topiramate can stimulate lipoprotein lipase in adipose tissue and skeletal muscles with a resultant increase in thermogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly enough, CA inhibitors demonstrate anti-cancer activity [19][20], because tumors rely on carbonic anhydrases (especially isoenzymes IX, XII, IV) in order to survive the acidic environment they create and sustain. Another aspect of the indiscriminate CA inhibition is the effect on the mitochondrial CA Va and CA Vb, which could result in less lipogenesis [21] of the cancer cells due to the diminished action of pyruvate carboxylase. De novo lipogenesis protects cancer cells from free radicals, minimizing membrane polyunsaturated fatty acids (PUFAS) [22].…”
Section: Discussionmentioning
confidence: 99%